Efeitos da laserterapia na atividade biológica de células de carcinoma epidermóide de língua humano - Henriques, àguida Cristina Gomes (2012)
The low level laser therapy (LLLT) has shown to be effective in promoting the proliferation of different cells in vitro, including keratinocytes, osteoblasts, endothelial cells and stem cells. It has been speculated that the biostimulatory effect of LLLT could cause undesirable enhancement of tumor growth in neoplastic diseases, since the malignant cells are more susceptible to proliferative stimuli. Within this context, this study evaluated the effect of LLLT on epidermoid carcinoma of the tongue cell line (SCC25) proliferation and invasion. Cultured cells were irradiated with an InGaAIP diode laser, 660nm, 30mW using two energy densities (0.5J/cm2 and 1.0J/cm2). Proliferative activity was assessed through trypan blue staining method and through cell cycle analysis using flow cytometry. The invasive potential was measured through cell invasion assay using matrigel. Cyclin D1, E-cadherin, -catenin and MMP-9 expressions were analyzed by immunofluorescence and flow cytometry and related to the investigated biological activities. Proliferation curve demonstrated that SCC25 irradiated with 1.0J/cm2 had the highest proliferative rate when compared to the control group and the group irradiated with 0.5J/cm2 (p<0.05). LLLT affected cell cycle distribution and energy density of 1.0 J/cm2 promoted a higher percentage of cells in S/G2/M phases, with statistically significant differences at 24h interval (p<0.05). LLLT, mainly with 1.0J/cm2, revealed significantly higher potential for invasion and influenced the expression of cyclin D1, E-cadherin, -catenin and MMP-9, promoting the malignant phenotype. In conclusion, our results indicate that LLLT has an important stimulatory effect on proliferation and invasion of SCC25 cells, likely due to altered expression of proteins associated with these processes